La cabane éclatée. Morcellement des objets immobiliers apparentés à l’art brut - Roberta Trapani (Les Cahiers de l'École du Louvre)
In the early 1930s, Jacques Brunius (1906-1967), poet and filmmaker, introduced the remarkable architecture of a rural postman from Hauterives, Ferdinand Cheval (1836-1924), to the surrealist group. From that time, a slow process of artistic recognition was given to structures similar to this site, dubbed a masterpiece and named the Palais Idéal. Artists, critics, researchers and curators contributed to helping bring about a new world of art. A hybrid world of art, related to that of art brut, made up of objects with no artistic pretensions to begin with and whose status has not stopped evolving according to definitions. What were the instruments of this process of "artification"? What was their impact on these in situ productions? From the landscape to the room of a museum, via an album or a magazine page, the article will examine certain stages in the social trajectory of these objects-places, which became collectors’ items.